REGULATION OF CABOTAGE PRINCIPLE TO GUARANTEE COASTAL STATE SOVEREIGNTY - nurfaika ishak; Meica Prameswari; Ade Darmawan B (Jurnal Hukum Replik, 2021)
This research tries to discuss the regulation of cabotage principle that is applied in Indonesia to protecting various aspects such as defense, trade/ economy, law, and social society. The purpose of this study is to examine the factor that influence the implementation of the cabotage principle. This study used a statutory approach and a conceptual approach. The method used is the normative and empirical. The results show that the concept of state sovereignty in advancing the national economy is a factor behind the application of cabotage principle. Inhibiting factors that affect the implementation of the cabotage principle are limitation of facilities and infrastructure owned by Indonesia in implementing this cabotage principle. The results of this study are expected to be useful for the application of the Cabotage principle in the Republic of Indonesia which is one of the largest maritime countrie in the world because Indonesia has the second longest coastline in the world after Canada